Kecerdasan Emosional Siswa Sekolah Dasar Negeri (SDN) dengan Siswa Sekolah Dasar Islam Terpadu (SDIT) di Kota Banda Aceh - Nurafni, Nurafni; Murnianti, Devi; Khairani, Maya (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2017)
Emotional intelligence is an ability for someone to control and recognise their own emotions and others’s. Emotional intelligence can be developed through education and school environment. The purpose this study is to know the difference of emotional intelligence between Public Elementary School and Islamic Private Elementary School in Banda Aceh. The quantitative method is used with purposive sampling technique, involving 256 students of fifth grade, within the range of age 10 to 11 years old, both girls and boys. The Study took place in two Public Elementary School and two Islamic Private Elementary School in Banda Aceh. The data was analyzed by using t-test independent samples, the result shows t-count 0,745 < t table 1,969 and p 0,457, that is means there is no difference of emotional intelligence between Public Elementary School and Islamic Private Elementary School in Banda Aceh.